Gene expression landscapes driving early life stages of the keystone seagrass Posidonia oceanica - Gianmarco Valenti; Alberto Sutera; Emanuela Dattolo; Francesco Cosenza; Francesco Carimi; Gabriele Procaccini; Francesco Mercati; Guglielmo Puccio; Roberto De Michele (Plant Cell Reports, 2026)
Key message Gene expression analyses reveal tissue-specific and temporally regulated networks driving Posidonia oceanica development, and identify key hub genes that coordinate root, leaf, and seed maturation. Abstract Seagrasses are marine angiosperms that form extensive underwater meadows, providing habitat, stabilising sediments, storing carbon, and protecting coastlines. Posidonia oceanica is the endemic foundation seagrass of the Mediterranean Sea, yet its meadows are rapidly declining. Despite its ecological importance, the molecular basis of P. oceanica development is still poorly understood. Here, we analysed gene expression in roots, leaves, and seeds across four developmental stages, revealing strong tissue-specific patterns and temporally regulated expression dynamics. Leaves exhibited active regulation of photosynthesis-related processes, while roots were enriched in pathways related to carbohydrate metabolism and cell wall biogenesis, supporting primary root growth and anchoring. The seeds retained metabolic activity, with glycolytic enzymes indicating readiness for germination. Temporal analyses identified a major transcriptional shift, with distinct gene sets sequentially activated during early establishment and late maturation in tissues. Weighted Gene Co-expression Network Analysis (WGCNA) identified modules strongly associated with specific tissues and developmental transitions, highlighting key hub genes involved in photosynthesis, metabolism, cell wall remodelling, and protein synthesis. Together, these results reveal complex, temporally coordinated regulatory networks underlying P. oceanica development .

Posidonia bonsai: Dwarf morphotypes of Posidonia oceanica in CO2 vents and non-vents areas suggest a novel growth strategy - Maria Cristina Gambi; Caterina Iacono; Antonino Miccio; Valentina Esposito; Gabriele Procaccini; Lazaro Marín-Guirao (Aquatic Botany, 2026)

Contrasting Genetic Diversity and Connectivity at the Eastern Range Edge of the Mediterranean Seagrass ( Posidonia oceanica ) - Daniela Haverbeck; Irene Olivé; Emanuela Dattolo; Mehmet Fatih Huseyinoglu; Paolo G. Albano; Gabriele Procaccini (Marine Ecology, 2025)
Populations at a species' distribution edges often present reduced gene flow, increased impact of genetic drift, and impoverished genetic variation, globally compromising their ability to adapt to environmental changes. This study assessed the genetic diversity, structure, and connectivity of the Mediterranean endemic seagrass Posidonia oceanica at its easternmost distribution limit, from diverse thermal regimes around Cyprus, contextualised within a set of 16 Turkish populations in the Levantine and Aegean Seas (eastern Mediterranean). The genetic assessments were based on sets of 13 to 16 microsatellite loci, depending on the analysis. Our findings revealed lower genotypic and allelic richness in the Cypriot populations, which also presented lower connectivity and higher differentiation among them in comparison to the Turkish ones. Additionally, the genetic and genotypic diversity and the connectivity of Cypriot populations were highly variable, with populations presenting high diversity and connectivity, while others exhibited extremely low diversity and high isolation. The discrepancies among the Cypriot populations were potentially due to differences in the sexual reproductive output related to the different thermal regimes around the island and the presence of barriers to gene flow along the island's southern coastline. This study advances our understanding of the genetic connectivity and genetic diversity of range‐edge P. oceanica populations in the Eastern Mediterranean. This knowledge can guide the management of conservation and ecosystem restoration initiatives for this habitat‐forming seagrass species.

Corrigendum to: “Transcriptome responses to single and combined stressors in seagrass populations from pristine and impacted sites reveal local adaptive features and core stress-response genes” [Sci. Total Environ. 987 (2025) 179623] - Hung Manh Nguyen; Beery Yaakov; Pedro Beca-Carretero; Gabriele Procaccini; Guannan Wang; Maheshi Dassanayake; Gidon Winters; Simon Barak (Science of The Total Environment, 2025)

Transcriptome responses to single and combined stressors in seagrass populations from pristine and impacted sites reveal local adaptive features and core stress-response genes - Hung Manh Nguyen; Beery Yaakov; Pedro Beca-Carretero; Gabriele Procaccini; Guannan Wang; Maheshi Dassanayake; Gidon Winters; Simon Barak (Science of The Total Environment, 2025)

The intensity of a field simulated marine heat wave differentially modulates the transcriptome expression of Posidonia oceanica from warm and cold environments - Patrizia Stipcich; Giulia Ceccherelli; Lázaro Marín-Guirao; Jessica Pazzaglia; Alex Santillán-Sarmiento; Gabriele Procaccini (Marine Biology, 2024)

Mass flowering and unprecedented extended pseudovivipary in seagrass (Posidonia oceanica) after a Marine Heat Wave - Fiona Tomas; Gema Hernan; Julia Mañez-Crespo; Andrés Arona; Daniela Haverbeck Meléndez; Xesca Reynés; Jonatan Delgado; Gabriele Procaccini; Enric Ballesteros (Marine Pollution Bulletin, 2024)

Marine heatwaves recurrence aggravates thermal stress in the surfgrass Phyllospadix scouleri - Manuel Vivanco-Bercovich; Jose Miguel Sandoval-Gil; Paula Bonet-Meliá; Alejandro Cabello-Pasini; Raquel Muñiz-Salazar; Leonardo Ruiz Montoya; Nadine Schubert; Lázaro Marín-Guirao; Gabriele Procaccini; Alejandra Ferreira-Arrieta (Marine Pollution Bulletin, 2024)

Climate change and the presence of invasive species will threaten the persistence of the Mediterranean seagrass community - Pedro Beca-Carretero; Gidon Winters; Mirta Teichberg; Gabriele Procaccini; Fabian Schneekloth; Ramon H. Zambrano; Kelcie Chiquillo; Hauke Reuter (Science of The Total Environment, 2024)

Ocean acidification impairs seagrass performance under thermal stress in shallow and deep water - Chiara Ravaglioli; Lucia De Marchi; Serena Anselmi; Emanuela Dattolo; Debora Fontanini; Carlo Pretti; Gabriele Procaccini; Gil Rilov; Monia Renzi; Jacob Silverman; Fabio Bulleri (Environmental Research, 2024)

Signs of local adaptation by genetic selection and isolation promoted by extreme temperature and salinity in the Mediterranean seagrass Posidonia oceanica - Hung Manh Nguyen; Miriam Ruocco; Emanuela Dattolo; Federica Paola Cassetti; Sebastiano Calvo; Agostino Tomasello; Lázaro Marín‐Guirao; Mathieu Pernice; Gabriele Procaccini (Molecular Ecology, 2023)
Adaptation to local conditions is known to occur in seagrasses; however, knowledge of the genetic basis underlying this phenomenon remains scarce. Here, we analysed Posidonia oceanica from six sites within and around the Stagnone di Marsala, a semi‐enclosed coastal lagoon where salinity and temperature exceed the generally described tolerance thresholds of the species. Sea surface temperatures (SSTs) were measured and plant samples were collected for the assessment of morphology, flowering rate and for screening genome‐wide polymorphisms using double digest restriction‐site‐associated DNA sequencing. Results demonstrated more extreme SSTs and salinity levels inside the lagoon than the outer lagoon regions. Morphological results showed significantly fewer and shorter leaves and reduced rhizome growth of P. oceanica from the inner lagoon and past flowering events were recorded only for a meadow farthest away from the lagoon. Using an array of 51,329 single nucleotide polymorphisms, we revealed a clear genetic structure among the study sites and confirmed the genetic isolation and high clonality of the innermost site. In all, 14 outlier loci were identified and annotated with several proteins including those relate to plant stress response, protein transport and regulators of plant‐specific developmental events. Especially, five outlier loci showed maximum allele frequency at the innermost site, likely reflecting adaptation to the extreme temperature and salinity regimes, possibly due to the selection of more resistant genotypes and the progressive restriction of gene flow. Overall, this study helps us to disentangle the genetic basis of seagrass adaptation to local environmental conditions and may support future works on assisted evolution in seagrasses.

The ontogeny-specific thermal sensitivity of the seagrass Posidonia oceanica - Alessandro Rinaldi; Marco Martinez; Fabio Badalamenti; Giovanni D’Anna; Simone Mirto; Lazaro Marín-Guirao; Gabriele Procaccini; Valeria Montalto (Frontiers in Marine Science, 2023)
Introduction The rapid increase in sea-water temperatures and frequency of extreme thermal events have amplified the risk of functional extinction of Mediterranean species such as the endemic long-lived seagrass Posidonia oceanica . Because of the valuable ecological functions and ecosystem services the species provides, understanding the life-stage specific thermal vulnerability is crucial to accurately predict the consequences of current and future global climate change and to protect and conserve existing meadows. Methods To this end, here we report a study on the ontogeny-specific thermal sensitivity of important physiological functions (i.e. respiration and net production) of three different early life history stages of P. oceanica , namely seed, seedling (4-month-old individuals) and 16-month-old plantlet by measuring thermal performance curves (eleven temperatures treatments between 15-36°C with n=8). Results All three stages examined showed photosynthetic activity during light exposure with similar optimal temperatures for both net and gross production. Gross photosynthesis increased with rising temperature up to 28-30°C, subsequently declining at higher temperatures until complete inhibition at 36°C. The metabolic response of seeds was found to be temperature-dependent up to 26°C, while respiration of seedlings and plantlets was almost stable up to 28-30°C, but increased markedly at higher temperatures, resulting in a negative whole-plant C balance at temperatures above 32°C. Overall, our results show that seedlings and plantlets tolerate a wider temperature range (15 - 32°C) than seeds, which experience metabolic and physiological dysfunction from 26-28°C onwards. Discussion These findings suggest that the impact of warming on recruitment in P. oceanica meadows may vary depending on the timing of marine heatwaves (i.e. mid-spring to mid-autumn) and provide useful knowledge to inform restoration programs using early life stages of the species. In conclusion, the study of physiological responses during the early life stages of species is key to identify life history stages that are particularly vulnerable to climate change, which is vital knowledge for ecosystem management and conservation.

Gene co-expression network analysis for the selection of candidate early warning indicators of heat and nutrient stress in Posidonia oceanica - Alex Santillán-Sarmiento; Jessica Pazzaglia; Miriam Ruocco; Emanuela Dattolo; Luca Ambrosino; Gidon Winters; Lázaro Marin-Guirao; Gabriele Procaccini (Science of The Total Environment, 2023)

Photo-physiology and morphology reveal divergent warming responses in northern and southern hemisphere seagrasses - Hung Manh Nguyen; Fabio Bulleri; Lázaro Marín-Guirao; Mathieu Pernice; Gabriele Procaccini (Marine Biology, 2021)

Partitioning resilience of a marine foundation species into resistance and recovery trajectories - Fernando Tuya; Yolanda Fernández-Torquemada; Yoana del Pilar-Ruso; Fernando Espino; Pablo Manent; Leticia Curbelo; Francisco Otero-Ferrer; Jose A. de la Ossa; Laura Royo; Laura Antich; Inés Castejón; Julia Máñez-Crespo; et al. (Oecologia, 2021)

Does Warming Enhance the Effects of Eutrophication in the Seagrass Posidonia oceanica? - Jessica Pazzaglia; Alex Santillán-Sarmiento; Stephanie B. Helber; Miriam Ruocco; Antonio Terlizzi; Lázaro Marín-Guirao; Gabriele Procaccini (Frontiers in Marine Science, 2020)
Seagrass meadows are disappearing at rates comparable to those reported for mangroves, coral reefs, and tropical rainforests. One of the main causes of their decline is the so-called cultural eutrophication, i.e., the input of abnormal amounts of nutrients derived from human activities. Besides the impact of eutrophication at a local scale, the occurrence of additional stress factors such as global sea warming may create synergisms in detriment of seagrass meadows’ health. In the present study, we aimed to evaluate if plants undergoing chronic cultural eutrophication and plants growing in relatively pristine waters are more (or less) sensitive to heat stress, nutrient load and the combination of both stressors. To address this question, a mesocosm experiment was conducted using Posidonia oceanica collected from two environments with different nutrients load history. Plants were exposed in controlled conditions to high nutrient concentrations, increased temperature and their combination for 5 weeks, to assess the effect of the single stressors and their interaction. Our results revealed that plants experiencing chronic cultural eutrophication (EU) are more sensitive to further exposure to multiple stressors than plants growing in oligotrophic habitats (OL). OL and EU plants showed different morphological traits and physiological performances, which corroborates the role of local pressures in activating different strategies in response to global environmental changes. EU-plants appeared to be weaker during the treatments, showing the greatest percentage of mortality, particularly under increased temperature. Temperature and nutrient treatments showed opposite effects when tested individually and an offset response when combined. The activation of physiological strategies with high energetic expenses to cope with excess of nutrients and other stressors, could affect plants present and future persistence, particularly under eutrophic conditions. Our results represent a step forward in understanding the complex interactions that occur in natural environments. Moreover, unraveling intraspecific strategies and the role of local acclimation/adaptation in response to multiple stressors could be crucial for seagrass conservation strategies under a climate change scenario.

The Tropical Seagrass Halophila stipulacea: Reviewing What We Know From Its Native and Invasive Habitats, Alongside Identifying Knowledge Gaps - Gidon Winters; Sven Beer; Demian A. Willette; Inés G. Viana; Kelcie L. Chiquillo; Pedro Beca-Carretero; Betty Villamayor; Tomás Azcárate-García; Rachamim Shem-Tov; Bridget Mwabvu; Luciana Migliore; Alice Rotini; et al. (Frontiers in Marine Science, 2020)

Heat‐stress induced flowering can be a potential adaptive response to ocean warming for the iconic seagrass Posidonia oceanica - Lazaro Marín‐Guirao; Laura Entrambasaguas; Juan M. Ruiz; Gabriele Procaccini (Molecular Ecology, 2019)
The Mediterranean Sea is particularly vulnerable to warming and the abrupt declines experienced by the endemic Posidonia oceanica populations after recent heatwaves have forecasted severe consequences for the ecological functions and socio‐economical services this habitat forming species provides. Nevertheless, this highly clonal and long‐lived species could be more resilient to warming than commonly thought since heat‐sensitive plants massively bloomed after a simulated heatwave, which provides the species with an opportunity to adapt to climate change. Taking advantage of this unexpected plant response, we investigated for the first time the molecular and physiological mechanisms involved in seagrass flowering through the transcriptomic analysis of bloomed plants. We also aimed to identify if flowering is a stress‐induced response as suggested from the fact that heat‐sensitive but not heat‐tolerant plants flowered. The transcriptomic profiles of flowered plants showed a strong metabolic activation of sugars and hormones and indications of an active transport of these solutes within the plant, most likely to induce flower initiation in the apical meristem. Preflowered plants also activated numerous epigenetic‐related genes commonly used by plants to regulate the expression of key floral genes and stress‐tolerance genes, which could be interpreted as a mechanism to survive and optimize reproductive success under stress conditions. Furthermore, these plants provided numerous molecular clues suggesting that the factor responsible for the massive flowering of plants from cold environments (heat‐sensitive) can be considered as a stress. Heat‐stress induced flowering may thus be regarded as an ultimate response to survive extreme warming events with potential adaptive consequences for the species. Fitness implications of this unexpected stress‐response and the potential consequences on the phenotypic plasticity (acclimation) and evolutionary (adaptation) opportunity of the species to ocean warming are finally discussed.

Temporal correlation of population composition and environmental variables in the marine invader Ciona robusta - Luigi Caputi; Francesco Toscano; Michele Arienzo; Luciano Ferrara; Gabriele Procaccini; Paolo Sordino (Marine Ecology, 2019)
The capacity for ascidians to inhabit coastal sea floor worldwide relies on their peculiar tolerance to environmental variables and pollution, which is considered, together with high levels of genetic diversity, among the main drivers of their invasive potential. In spite of the continued interest in the genetics of invasive species, little attention has been paid toward the microevolutionary processes that drive structure and fate of ascidian populations over time under chemically polluted conditions. Understanding the interplay between environmental and population dynamics is critical to predict the biodiversity of marine coastal ecosystems. In the present study, a local population of the ascidian Ciona robusta living in the Fusaro Lagoon has been monitored over a 13‐month period of sampling. Physico‐chemical parameters (temperature, salinity, turbidity, dissolved oxygen, heavy metals), genetic composition (microsatellites, ITS‐2), abundance and biomass (wet and dry weight) were assessed with the aim to infer fine‐scale temporal variation of population structure with respect to rapid environmental change. Analysis of biomass showed that C. robusta is highly sensitive to salinity and oxygen concentrations. Further, genetic analysis suggested a highly dynamic population structure, likely due to the strong clustering of temporal samples and distinct responses to environmental conditions, including bioaccumulation of heavy metals. Here, we hypothesize that rapid variation in allele frequencies of neutral markers in C. robusta populations may increase the ability of the species to colonize habitats that are subject to strong variation and are under heavy human pressure.

Within- and among-leaf variations in photo-physiological functions, gene expression and DNA methylation patterns in the large-sized seagrass Posidonia oceanica - Miriam Ruocco; Lázaro Marín-Guirao; Gabriele Procaccini (Marine Biology, 2019)

Molecular level responses to chronic versus pulse nutrient loading in the seagrass Posidonia oceanica undergoing herbivore pressure - Miriam Ruocco; Lázaro Marín-Guirao; Chiara Ravaglioli; Fabio Bulleri; Gabriele Procaccini (Oecologia, 2018)

Seagrass collapse due to synergistic stressors is not anticipated by phenological changes - Giulia Ceccherelli; Silvia Oliva; Stefania Pinna; Luigi Piazzi; Gabriele Procaccini; Lazaro Marin-Guirao; Emanuela Dattolo; Roberto Gallia; Gabriella La Manna; Paola Gennaro; Monya M. Costa; Isabel Barrote; et al. (Oecologia, 2018)

Genomewide transcriptional reprogramming in the seagrass Cymodocea nodosa under experimental ocean acidification - Miriam Ruocco; Francesco Musacchia; Irene Olivé; Monya M. Costa; Isabel Barrote; Rui Santos; Remo Sanges; Gabriele Procaccini; João Silva (Molecular Ecology, 2017)
Here, we report the first use of massive‐scale RNA ‐sequencing to explore seagrass response to CO 2 ‐driven ocean acidification ( OA ). Large‐scale gene expression changes in the seagrass Cymodocea nodosa occurred at CO 2 levels projected by the end of the century. C. nodosa transcriptome was obtained using Illumina RNA ‐Seq technology and de novo assembly, and differential gene expression was explored in plants exposed to short‐term high CO 2 /low pH conditions. At high p CO 2 , there was a significant increased expression of transcripts associated with photosynthesis, including light reaction functions and CO 2 fixation, and also to respiratory pathways, specifically for enzymes involved in glycolysis, in the tricarboxylic acid cycle and in the energy metabolism of the mitochondrial electron transport. The upregulation of respiratory metabolism is probably supported by the increased availability of photosynthates and increased energy demand for biosynthesis and stress‐related processes under elevated CO 2 and low pH . The upregulation of several chaperones resembling heat stress‐induced changes in gene expression highlighted the positive role these proteins play in tolerance to intracellular acid stress in seagrasses. OA further modifies C. nodosa secondary metabolism inducing the transcription of enzymes related to biosynthesis of carbon‐based secondary compounds, in particular the synthesis of polyphenols and isoprenoid compounds that have a variety of biological functions including plant defence. By demonstrating which physiological processes are most sensitive to OA , this research provides a major advance in the understanding of seagrass metabolism in the context of altered seawater chemistry from global climate change.

Respiratory oxygen consumption in the seagrass Zostera marina varies on a diel basis and is partly affected by light - Lina M. Rasmusson; Chiara Lauritano; Gabriele Procaccini; Martin Gullström; Pimchanok Buapet; Mats Björk (Marine Biology, 2017)

High connectivity and directional gene flow in European Atlantic and Mediterranean populations of Ciona intestinalis sp. A - Ornella Affinito; Nikos Andreakis; Luigi Caputi; Rita Marino; Raimondo Pannone; Paolo Sordino; Gabriele Procaccini (Marine Ecology, 2015)
Understanding the factors that cause population divergence has long been of interest to marine biologists in their attempts to interpret the effect of human‐mediated vectors. Broadcast‐spawning species with limited dispersal capability are excellent candidates to measure the present‐day patterns of genetic diversity. The tunicate Ciona intestinalis (Ascidiacea) is comprised of a complex of morphologically cryptic species that form vigorous aggregates in eutrophic habitats (harbors, gulfs and lagoons) where they can compete with the epibenthic community and cause biofouling problems. This study investigated biogeographic variability and migration patterns of C. intestinalis sp. A along Northeast Atlantic and Mediterranean coasts using microsatellite markers. Data presented here on 371 specimens collected from 17 populations reveal high genetic polymorphism, but with a deficit of heterozygote deficiency. Absence of evidence for isolation by distance suggests that the genetic patterns do not reflect the geographic distribution of sampled populations. Substantial gene flow and artificial potential for dispersal boost high levels of within‐population genetic variability and prevent genetic differentiation within and between seas. A predominant eastward migration pattern was revealed by the data set, with very limited opportunity for C. intestinalis sp. A to travel westward. This directional movement indicates that other properties ( e.g . habitat quality, genetic traits, mating system, life cycle) may cause adaptive divergence at a large biogeographic scale.

A meta‐analysis reveals a positive correlation between genetic diversity metrics and environmental status in the long‐lived seagrass P osidonia oceanica - Marlene Jahnke; Jeanine L. Olsen; Gabriele Procaccini (Molecular Ecology, 2015)
The seagrass P osidonia oceanica is a key engineering species structuring coastal marine systems throughout much of the M editerranean basin. Its decline is of concern, leading to the search for short‐ and long‐term indicators of seagrass health. Using A rc GIS maps from a recent, high‐resolution (1–4 km) modelling study of 18 disturbance factors affecting coastal marine systems across the M editerranean (Micheli et al . 2013, http://globalmarine.nceas.ucsb.edu/mediterranean/ ), we tested for correlations with genetic diversity metrics (allelic diversity, genotypic/clonal diversity and heterozygosity) in a meta‐analysis of 56 meadows. Contrary to initial predictions, weak but significantly positive correlations were found for commercial shipping, organic pollution (pesticides) and cumulative impact. This counterintuitive finding suggests greater resistance and resilience of individuals with higher genetic and genotypic diversity under disturbance (at least for a time) and/or increased sexual reproduction under an intermediate disturbance model. We interpret the absence of low and medium levels of genetic variation at impacted locations as probable local extinctions of individuals that already exceeded their resistance capacity. Alternatively, high diversity at high‐impact sites is likely a temporal artefact, reflecting the mismatch with pre‐environmental impact conditions, especially because flowering and sexual recruitment are seldom observed. While genetic diversity metrics are a valuable tool for restoration and mitigation, caution must be exercised in the interpretation of correlative patterns as found in this study, because the exceptional longevity of individuals creates a temporal mismatch that may falsely suggest good meadow health status, while gradual deterioration of allelic diversity might go unnoticed.

A new set of pure microsatellite loci in the common octopus Octopus vulgaris Cuvier, 1797 for multiplex PCR assay and their cross-amplification in O. maya Voss & Solís Ramírez, 1966 - Daniele De Luca; Gaetano Catanese; Graziano Fiorito; Gabriele Procaccini (Conservation Genetics Resources, 2015)

Seagrass ecophysiology meets ecological genomics: are we ready? - Gabriele Procaccini; Sven Beer; Mats Björk; Jeanine Olsen; Silvia Mazzuca; Rui Santos (Marine Ecology, 2012)
In March 2011, the Ecophysiology and Genetics Working Groups of the European Science Foundation COST Action ES 0906, entitled Seagrass Productivity: From Genes to Ecosystem Management , organized an exploratory workshop entitled “Linking Ecophysiology and Ecogenomics in Seagrass Systems”. The goal of the workshop was to discuss how to integrate comparative gene expression studies with physiological processes such as photosynthetic performance, carbon and nitrogen utilization and environmental adaptation. The main questions discussed for integrative research related to mechanisms of carbon utilization, light requirements, temperature effects and natural variation in pH and ocean acidification. It was concluded that the seagrass research community is still in the nascent stages of linking ecophysiology with genomic responses, as carbon and nitrogen metabolism of seagrasses have not been sufficiently well studied. Likewise, genomic approaches have only been able to assign meaningful interpretations to a handful of differentially expressed genes. Nevertheless, the way forward has been established.

Reference genes assessment for the seagrass Posidonia oceanica in different salinity, pH and light conditions - Ilia Anna Serra; Chiara Lauritano; Emanuela Dattolo; Andrea Puoti; Silvia Nicastro; Anna Maria Innocenti; Gabriele Procaccini (Marine Biology, 2012)

Seagrass meadows at the extreme of environmental tolerance: the case of Posidonia oceanica in a semi‐enclosed coastal lagoon - Agostino Tomasello; Germana Di Maida; Sebastiano Calvo; Maria Pirrotta; Marco Borra; Gabriele Procaccini (Marine Ecology, 2009)
Atoll‐like structures of the endemic Mediterranean seagrass Posidonia oceanica were encountered in the innermost area of the Stagnone di Marsala, a semi‐enclosed coastal lagoon along the western coasts of Sicily. The area is characterized by limited water exchange with the open sea and by a marked seasonal variation of water salinity and temperature, reaching beyond the theoretical tolerance limits of the species. In the present study we determined the genetic composition of the atoll‐like structures, as well as the growth performance and flowering rate of these stands. We also assessed whether and to what extent the atoll‐like structures are genetically isolated from plants growing in meadows outside the lagoon. For this purpose we utilized 13 microsatellite markers to genotype single shoots sampled inside and outside the lagoon. Lepidochronological analyses were performed on the same shoots to determine the annual rhizome growth rate, the number of leaves and the inflorescences formed as an estimate of growth‐ and reproductive performance over the years. The innermost area of the lagoon showed a lower number of alleles, a lower percentage of polymorphic loci, a lower clonal diversity, but higher heterozygosis excess with respect to the other areas analysed. Spatial autocorrelation was here significant, up to slightly below 300 m. Shoots collected in the atolls exhibited a 25% lower vertical growth rate and 16% lower leaf formation in comparison to those in open‐sea meadows. No flowering events were recorded during 24 years of investigation, whereas inflorescences were observed frequently in meadows outside the lagoon. Results from F st and factorial correspondence analysis confirmed the expected genetic isolation of the confined atolls with respect to the meadows outside the lagoon and revealed limited gene flow within the lagoon itself. Apparently, the enclosed system of the Stagnone lagoon is genetically isolated, with a possible selection of genotypes adapted to persistent stressful conditions, consistent with reduced growth and lack of flowering events.

High genetic diversity and connectivity in the polyploid invasive seaweed Asparagopsis taxiformis (Bonnemaisoniales) in the Mediterranean, explored with microsatellite alleles and multilocus genotypes - NIKOS ANDREAKIS; WIEBE H. C. F. KOOISTRA; GABRIELE PROCACCINI (Molecular Ecology, 2009)
The red alga, Asparagopsis taxiformis , has recently expanded its distribution range into the Western Mediterranean Sea, and populations have now even been found on the Portuguese South coast. All Western Mediterranean populations belong to a single mitochondrial cryptic lineage (referred to as lineage 2 in earlier studies) and probably result from a recent invasion of Indo‐Pacific origin. Here we investigate fine‐scale population genetic diversity and structure within and among Mediterranean populations of lineage 2 using eight microsatellite loci and compare the obtained patterns with those observed in a Californian population of the same lineage. To generate an appropriate analytical method suitable to the polyploid status of this species, we score microsatellite loci as in a dominant marker system. Thereafter, we produce robust descriptors inferred from frequencies of both microsatellite alleles and multilocus genotypes. Populations from California and the Mediterranean Sea differ considerably in their levels of genetic diversity. In the Mediterranean, populations reproduce predominantly sexually and exhibit high levels of genotypic variation, suggestive either of multiple introductions or of a single introduction by a genetically diverse and large group of individuals. Bayesian clustering revealed one or possibly two weakly supported panmictic subpopulations, indicative of extensive admixture. The expansion of this lineage is rapid, possibly due to the absence of eco–physiological barriers to gene flow throughout its invasive trajectory.

Phylogeography of the invasive seaweed Asparagopsis (Bonnemaisoniales, Rhodophyta) reveals cryptic diversity - NIKOS ANDREAKIS; GABRIELE PROCACCINI; CHRISTINE MAGGS; WIEBE H. C. F. KOOISTRA (Molecular Ecology, 2007)
The rhodophyte seaweed Asparagopsis armata Harvey is distributed in the northern and southern temperate zones, and its congener Asparagopsis taxiformis (Delile) Trevisan abounds throughout the tropics and subtropics. Here, we determine intraspecific phylogeographic patterns to compare potential causes of the disjunctions in the distributions of both species. We obtained specimens throughout their ranges and inferred phylogenies from the hypervariable domains D1‐D3 of the nuclear rDNA LSU, the plastid spacer between the large and small subunits of RuBisCo and the mitochondrial cox 2–3 intergenic spacer. The cox spacer acquired base changes the fastest and the RuBisCo spacer the slowest. Median‐joining networks inferred from the sequences revealed the absence of phylogeographic structure in the introduced range of A. armata , corroborating the species’ reported recent introduction. A. taxiformis consisted of three nuclear, three plastid and four mitochondrial genetically distinct, lineages (1–4). Mitochondrial lineage 3 is found in the western Atlantic, the Canary Islands and the eastern Mediterranean. Mitochondrial lineages 1, 2, and 4 occur in the Indo‐Pacific, but one of them (lineage 2) is also found in the central Mediterranean and southern Portugal. Phylogeographic results suggest separation of Atlantic and Indo‐Pacific lineages resulted from the emergence of the Isthmus of Panama, as well as from dispersal events postdating the closure event, such as the invasion of the Mediterranean Sea by mitochondrial lineages 2 and 3. Molecular clock estimates using the Panama closure event as a calibration for the split of lineages 3 and 4 suggest that A. taxiformis diverged into two main cryptic species (1 + 2 and 3 + 4) about 3.2–5.5 million years ago (Ma), and that the separation of the mitochondrial lineages 1 and 2 occurred 1–2.3 Ma.

Vicariance patterns in the Mediterranean Sea: east–west cleavage and low dispersal in the endemic seagrass Posidonia oceanica - Sophie Arnaud‐Haond; Marianna Migliaccio; Elena Diaz‐Almela; Sara Teixeira; Mirjiam Susanne Van De Vliet; Filipe Alberto; Gabriele Procaccini; Carlos M. Duarte; Ester A. Serrão (Journal of Biogeography, 2007)
Aim The seagrass, Posidonia oceanica is a clonal angiosperm endemic to the Mediterranean Sea. Previous studies have suggested that clonal growth is far greater than sexual recruitment and thus leads to low clonal diversity within meadows. However, recently developed microsatellite markers indicate that there are many different genotypes, and therefore many distinct clones present. The low resolution of markers used in the past limited our ability to estimate clonality and assess the individual level. New high‐resolution dinucleotide microsatellites now allow genetically distinct individuals to be identified, enabling more reliable estimation of population genetic parameters across the Mediterranean Basin. We investigated the biogeography and dispersal of P. oceanica at various spatial scales in order to assess the influence of different evolutionary factors shaping the distribution of genetic diversity in this species. Location The Mediterranean. Methods We used seven hypervariable microsatellite markers, in addition to the five previously existing markers, to describe the spatial distribution of genetic variability in 34 meadows spread throughout the Mediterranean, on the basis of an average of 35.6 (± 6.3) ramets sampled. Results At the scale of the Mediterranean Sea as a whole, a strong east–west cleavage was detected ( amova) . These results are in line with those obtained using previous markers. The new results showed the presence of a putative secondary contact zone at the Siculo‐Tunisian Strait, which exhibited high allelic richness and shared alleles absent from the eastern and western basins. F statistics (pairwise θ ranges between 0.09 and 0.71) revealed high genetic structure between meadows, both at a small scale (about 2 to 200 km) and at a medium scale within the eastern and western basins, independent of geographical distance. At the intrameadow scale, significant spatial autocorrelation in six out of 15 locations revealed that dispersal can be restricted to the scale of a few metres. Main conclusions A stochastic pattern of effective migration due to low population size, turnover and seed survival is the most likely explanation for this pattern of highly restricted gene flow, despite the importance of an a priori seed dispersal potential. The east–west cleavage probably represents the outline of vicariance caused by the last Pleistocene ice age and maintained to this day by low gene flow. These results emphasize the diversity of evolutionary processes shaping the genetic structure at different spatial scales.

Temporal variations in the spatial distribution of shoot density in a Posidonia oceanica meadow and patterns of genetic diversity - Valerio Zupo; Maria Cristina Buia; Maria Cristina Gambi; Maurizio Lorenti; Gabriele Procaccini (Marine Ecology, 2006)
The meadows of the Mediterranean endemic seagrass Posidonia oceanica exhibit relatively high variations of structural and biometric features at various spatial scales. An investigation performed in 1992 in the meadow off Lacco Ameno (Island of Ischia, Gulf of Naples, Italy) detected peculiar spatial patterns of plant distribution, characterized by nestlike structures with radially increasing or decreasing shoot densities. Eight years later (2000), geo‐referenced collections at selected points were repeated to trace the temporal variations of shoot density and investigate the recurrence of the density cores previously detected. In addition, shoots for molecular analyses were collected to check the hypothesis that nestlike patterns exhibit highest levels of genetic variability, due to the confluence of several genetically distinct stolons. The 2000 survey confirmed the presence of the main density cores detected in 1992, although their spatial distribution was slightly shifted and a general decrease of spatial anisotropy was observed, probably due to an increased disturbance, mainly due to pleasure boat anchoring. Patterns of genetic diversity showed a more complex picture, well related to the shoot density spatial pattern, especially when compared with the previous 1992 survey. Patterns of genetic diversity confirmed our previous hypotheses on the genesis of shoot density cores, suggesting they are produced over long time, due to a slow stolonization process and a convergence of different genotypes. Regression of the meadow and decrease of density may lead, in short periods, to a homogenization of the density patterns, while genetic diversity cores represent a long‐term ‘memory’ of their previous distribution.

A tribute to Lucia Mazzella (1947–1999) - Maria Cristina Buia; Gabriele Procaccini; Maria Cristina Gambi (Marine Ecology, 2006)

Mating System and Clonal Architecture: A Comparative Study in Two Marine Angiosperms - Maria Valeria Ruggiero; Stefano Capone; Patrizia Pirozzi; Thorsten B. H. Reusch; Gabriele Procaccini (Evolutionary Ecology, 2005)

North Atlantic phylogeography and large‐scale population differentiation of the seagrass Zostera marina L. - JEANINE L. OLSEN; WYTZE T. STAM; JAMES A. COYER; THORSTEN B. H. REUSCH; MARTIN BILLINGHAM; CHRISTOFFER BOSTRÖM; ELIZABETH CALVERT; HARTVIG CHRISTIE; STEPHEN GRANGER; RICHARD LA LUMIÈRE; NATALIYA MILCHAKOVA; MARIE‐PIERRE OUDOT‐LE SECQ; et al. (Molecular Ecology, 2004)
As the most widespread seagrass in temperate waters of the Northern Hemisphere, Zostera marina provides a unique opportunity to investigate the extent to which the historical legacy of the last glacial maximum (LGM18 000–10 000 years bp ) is detectable in modern population genetic structure. We used sequences from the nuclear rDNA–internal transcribed spacer (ITS) and chloroplast mat K‐intron, and nine microsatellite loci to survey 49 populations (> 2000 individuals) from throughout the species’ range. Minimal sequence variation between Pacific and Atlantic populations combined with biogeographical groupings derived from the microsatellite data, suggest that the trans ‐Arctic connection is currently open. The east Pacific and west Atlantic are more connected than either is to the east Atlantic. Allelic richness was almost two‐fold higher in the Pacific. Populations from putative Atlantic refugia now represent the southern edges of the distribution and are not genetically diverse. Unexpectedly, the highest allelic diversity was observed in the North Sea–Wadden Sea–southwest Baltic region. Except for the Mediterranean and Black Seas, significant isolation‐by‐distance was found from ~150 to 5000 km. A transition from weak to strong isolation‐by‐distance occurred at ~150 km among northern European populations suggesting this scale as the natural limit for dispersal within the metapopulation. Links between historical and contemporary processes are discussed in terms of the projected effects of climate change on coastal marine plants. The identification of a high genetic diversity hotspot in Northern Europe provides a basis for restoration decisions.

The rDNA ITS Region in the Lessepsian Marine Angiosperm Halophila stipulacea (Forssk.) Aschers. (Hydrocharitaceae): Intragenomic Variability and Putative Pseudogenic Sequences - Maria Valeria Ruggiero; Gabriele Procaccini (Journal of Molecular Evolution, 2004)

Isolation and characterization of microsatellite loci in the ascidian Ciona intestinalis (L.) - Gabriele Procaccini; Michele Pischetola; Roberto Di Lauro (Molecular Ecology, 2000)